1986
DOI: 10.1175/1520-0477(1986)067<0825:facfso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fog-82: A Cooperative Field Study of Radiation Fog

Abstract: The Cloud Physics Section of the Atmospheric Sciences Research Center-State University of New York at Albany conducted a cooperative field study (FOG-82) during the autumn of 1982 as part of an ongoing radiation-fog research program. A computer-controlled data-acquisition system consisting of sophisticated soil, surface, and boundary-layer sensors, as well as contemporary aerosol and drop-let probes was developed. These data are being used to address a variety of critical problems related to radiation-fog evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Several field experiments have been carried out since the 1970s and have contributed to the important progress made in understanding fog processes. Noteworthy studies include campaigns at Cardington in the UK (Roach et al, 1976;; Fog-82 in Albany, New York (Meyer et al, 1986); Lille 91 in France (Guedalia and Bergot, 1994); a campaign in the Po valley in Italy (Fuzzi et al, 1998) and ParisFog in France (Haeffelin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several field experiments have been carried out since the 1970s and have contributed to the important progress made in understanding fog processes. Noteworthy studies include campaigns at Cardington in the UK (Roach et al, 1976;; Fog-82 in Albany, New York (Meyer et al, 1986); Lille 91 in France (Guedalia and Bergot, 1994); a campaign in the Po valley in Italy (Fuzzi et al, 1998) and ParisFog in France (Haeffelin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It usually forms near the surface under clear skies in stagnant air in association with anticyclonic conditions (Gultepe et al, 2007). However, the mechanisms of radiation fog formation, development and dissipation are very complex and have been extensively studied with a series of numerical simulations and comprehensive observational programs including in situ measurements (Meyer et al, 1986;Fitzjarrald and Lala, 1989;Fuzzi et al, 1992Fuzzi et al, , 1998Gultepe et al, 2007;Zhou and Ferrier, 2008;Liu et al, 2011;Dupont et al, 2012). Recently, field experiments have been conducted to investigate dynamic, thermodynamic, microphysical, and radiative processes in Beijing and Nanjing, China (Liu et al, 2011), in Canada (Gultepe et al, 2009), and in Paris, France (Haeffelin et al, 2010;Dupont et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Especially for fog and low stratus clouds, several authors have identified different evolutionary stages with strong influences on the drop size spectrum and thus the relationship between Z and LWC (e.g. Pilié et al 1975b, MEYER et al 1986, WELCH and RAVICHANDRAN 1986, WENDISCH et al 1998.…”
Section: Introductionmentioning
confidence: 99%